Managing the psychological contract : using the personal deal to increase business performance - Wellin, Michael (Gower, 2007)
This is the first book which shows how the psychological contract can be used in practice. Michael Wellin reinterprets the psychological contract as something very tangible that exists between people at work and indicates how it can be used to increase business performance, improve employee commitment, and enable employees to realise their potential. Throughout the book, the author combines the latest organisation behaviour research findings, including those on the psychological contract, with his own and colleagues' experiences, to provide an important and extremely readable book for human re.